Non-state violent actors and social movement organizations : influence, adaptation, and change - Mazzei, Julie; Coy, Patrick G. (Bingley : Emerald Publishing Limited, 2017)
This volume focusses on non-state actors and political conflicts but also attends to the broader themes of the series. The research emphases the roles and motivations of non-state actors in conflicts or post-conflict situations in the post-Cold War era; as well outlining the dynamics of social movements, conflicts, or change. This volume highlights the motivations and interests of non-state violent actors (NSVAs) in the post-Cold War era; the role of identity and/or ideology in the conflicts or resolutions of so-called'new wars;' the impact of NSVAs in conflict and/or peace-making; and the ways in which IGOs and NGOs interact with NSVAs in conflicts or post-conflict zones.
Prelims -- Section I: Non-state actors : influence and adaptation in conflict environments -- Section II: Non-state actors : challengers and change -- About the authors -- Index.
Includes index.
Keywords: Social movements; Social Science -- Demography; Demonstrations & protest movements